Congenital midline cervical cleft - A case report on a rare anomaly of the neck - C S Vidhya Annapoorni; Sam Varkey (Wolters Kluwer Medknow Publications, 2022)
Congenital midline cervical cleft is a rare congenital anomaly of the neck of uncertain embryological origin, with around 205 cases reported in literature. We report the case of an 8-year-old girl who presented with the same anomaly.